The efficacy of specific patterns of movements and brain exercises on the cognitive performance of healthy senior citizen in Jakarta (Medical Journal of Indonesia, 2003)
The objective of this study was to determine the efficacy of brain movement and exercise in healthy senior subjects. Brain movement and exercise or Gerak dan Latih Otak (GLO) which comprised of muscles stretching, breathing exercise, and crossing the body's midline of the eyes, head and extremities were performed two times weekly for two months by 70 normal healthy senior subjects. A pre- and posttest on 5 cognitive performance, consisted of visual scanning and tracking (VST), delayed recall (DR), verbal fluency (VF), digits backward (DB), and trail making test-B (TMT-B). The age range of the subjects was 48 to 70 years and duration of education ranged from 6 to 18 years or more. The results of the statistical analyses showed that all the subjects showed high significant increase performance on the five cognitive domains. Women performed significantly in all the tests, while in men the significant increase was on VST, DR, and TMT-B. No different significant increase cognitive performance could be obtained between the two age groups (below 60 years and 60 years upward) and level of education, except for the high education group. It is suggested that further studies with larger scale subjects and same methodology should be performed in several places in Indonesia. (Med J Indones 2003; 12: 155-61)